ANALYSIS OF INVESTMENT FEASIBILITY STUDY USING THE CAPITAL BUDGETING METHOD AT SAMUDRA WORKSHOP BUSINESS IN LUMAJANG - Alfiani Umi Namiroh; Nuntupa Nuntupa; Cici Widya Prasetyandari (Ecobankers : Journal of Economy and Banking, 2026)
This study aims to analyze the investment feasibility of Bengkel Samudra Motor, an automotive service business located in Lumajang Regency, East Java. The primary objective is to evaluate whether investing in the business expansion will provide financially and operationally viable returns. Method of analysis employed is the capital budgeting method, which includes Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period. In addition, non-financial and SWOT analyses were conducted to obtain a more holistic perspective. The findings indicate that the business generates an average annual revenue of Rp750,000,000 with a net profit margin of 70%, resulting in an annual net income of Rp525,000,000. The NPV is calculated at Rp1,739,254,000, IRR reaches 160%, and the Payback Period is 6 months, suggesting that the investment is highly profitable and feasible. From a non-financial perspective, the business demonstrates strong customer loyalty, consistent customer growth, and a commitment to technological advancement. The SWOT analysis reveals that internal strengths such as stable income and strong reputation, as well as opportunities in digital expansion, can be leveraged to address threats like new competitors and cost fluctuations.In conclusion, investing in Bengkel Samudra Motor is not only financially feasible but also strategically promising in the long term. It is recommended that the management initiate business expansion and service digitalization to enhance competitiveness in the future.